Design, optimisation and validation of molecular diagnostic assays for BRAF p.Val600Glu and associated genetic factors within hairy cell leukemia (HCL) and HCL-like entities at Tygerberg Hospital, South Africa - Mhlongo, Zwelakhe Johan Michael (Stellenbosch: Stellenbosch University, 2025)
Thesis (MMed)--Stellenbosch University, 2025.